Penggunaan modul pembelajaran Kemahiran Jawi - Mohamad @ Mohd. Noor, Nazimah (2014)
This study was conducted to determine secondary school students' achievement and interest in Jawi skills through the use of Jawi skill learning modules developed by the researcher. The participants were form one students were selected by the school and then divided into two groups. The first group of 30 students were classified as the experimental group and the second group of 30 were classified as the control group. The experimental group had their teaching and learning process with the researcher whiles the control group had their teaching and learning process with the Islamic Education teacher of the school. These two group were distinguished in the way they learn Jawi skills. The experimental group used the Jawi sklls learning modules and the control group was using the school-based assessment (PBS) modules. Each group was to answer the pre and post questionnaire as well as the pre and post test in each part of the module. Data were collected and analyzed usng SPSS version 16.0. The value of Cronbach Alpha foe the questionnaire items for the pilot study conducted was 0.785. The study found a significant difference between the pre and post test for achievement of experimental group. However, there was no significant difference between pre and post test for interest in Jawi skills. The report also found a number of implications forparents, school and secondary school students. Recommendations for futher research are also proposed at the end of the study.